2019
DOI: 10.1177/0002716219831947
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Work Attitudes and Values: Comparisons, Consequences, and Implications

Abstract: Are attitudes toward work and perceptions of the benefits of work transmitted from parents to youth similarly across a variety of cultural contexts? What determines the centrality of work to one's life? How are intrinsic work values (intangible rewards such as autonomy, learning opportunities, and self-fulfillment) and extrinsic work values (such as status, income, and financial safety) shaped; and how do these work attitudes have consequences in the political, economic, and wellbeing domains? Are the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The analysis of the LFS allows us to observe the intergenerational transmission of the failure or success of young people in relation to the labor market: young people whose parents (father) have a lower education level and who come from large families have a higher risk of being NEETs. The results of our analysis are in agreement with other studies on the European level that examined the effect of both maternal and paternal employment on the success or failure of their children in the labor market (Berloffa et al, 2015;Cemalcilar et al, 2019;Kraaykamp et al, 2019;McDowell, 2014). Controlling for other variables (education, social environment), researchers found that the effect of parental employment (both mother and father) increases the likelihood of their sons and daughters getting a job.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
“…The analysis of the LFS allows us to observe the intergenerational transmission of the failure or success of young people in relation to the labor market: young people whose parents (father) have a lower education level and who come from large families have a higher risk of being NEETs. The results of our analysis are in agreement with other studies on the European level that examined the effect of both maternal and paternal employment on the success or failure of their children in the labor market (Berloffa et al, 2015;Cemalcilar et al, 2019;Kraaykamp et al, 2019;McDowell, 2014). Controlling for other variables (education, social environment), researchers found that the effect of parental employment (both mother and father) increases the likelihood of their sons and daughters getting a job.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
“…Following existing research in this area, we distinguish between intrinsic and extrinsic work values (Kalleberg & Marsden, 2019;Kraaykamp et al, 2019). The ESS contains questions for both types of work values.…”
Section: Dependent Variablementioning
confidence: 99%
“…Values are internalized social representations or moral beliefs that people call on to rationalize their actions (Oyserman 2002). Work values, more specifically, refer to individuals’ attitudes about how important work is and whether individuals pursue tangible or intangible rewards in their jobs (see Kraaykamp, Cemalcilar, and Tosun, this volume). Empirical research in the social sciences has shown that work values predict a variety of work-related outcomes, including vocational aspirations, career choices, decision-making processes such as to look for a job, or to get training, job selection, as well as job satisfaction (e.g., Ros, Schwartz, and Surkiss 1999).…”
mentioning
confidence: 99%